The enhancement of laminar jet cooling effectiveness at very high surface temperature by using Al2O3 nanofluid as a coolant. Issue 3 (27th January 2020) - Barik, Kashinath; Chitransh, Susmit; Pati, A. R.; Swain, B.; Behera, Ajit; Mohapatra, S. S.
Abstract: In the current study, as per the requirement of various metal quenching industries, high heat removal rate, low consumption rate of the coolant, and the minimum operating cost of the process have been tried to be achieved in the Leidenfrost region by using a nanofluid low mass flux laminar jet. In this regard, an indigenously designed and fabricated experimental setup was used and before experimentation, the coolant (Al2 O3 +Water) thermophysical properties variation was monitored for the mapping of the transfer characteristics during the cooling process. The thermal analysis discloses that the critical heat flux (CHF) depicts a trend with the rising nanoparticle concentration in the mixture; however, at the medium concentration (0.10% Al2 O3 ) except the CHF region, in the remaining region, better heat removal rate is observed. The comparison of the current cooling methodology with that reported in literature clearly approves that the proposed process methodology mitigates the requirements described above.